The Effect of Lifestyle, Spiritual, and Family Support on Diabetic Mellitus Patient with Chronic Kidney Disease Complication - Anwar Rosyadi; Indri Hapsari; Pri Iswati Utami (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
Patients with Diabetes Mellitus (DM) with complications of chronic kidney disease (CKD) have decreased quality of life (QOL). Some factors that can affect QOL are lifestyle, spirituality, and family support. The purpose of this study was to determine the effect of lifestyle, spirituality, and family support on the QOL of DM patients with CKD complications at Siaga Medika Purbalingga Hospital. Respondents from this study were all patients diagnosed with DM with CKD complications and had a history of treatment in August 2019-September 2020 period. A total of 48 respondents then filled out a questionnaire that had been tested for validity and reliability. The results of this study are respondents have a good quality of life as much as 62.5%, and the remaining 32.5% are not good. Patients who have a better lifestyle and spiritual level have 11 times the chance of having a better QOL. Meanwhile, patients who have better family support have a 0.13 times better chance of their QOL. In conclusion, there is a significant impact between lifestyle, spirituality, and family support with QOL. Hospitals are urgently needed in providing counseling about the importance of lifestyle, spirituality level and family support so that the patient's QOL increases.